2009
DOI: 10.5254/1.3557001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effect of the Migration of A Paraffin Wax on the Surface Free Energy of Natural Rubber

Abstract: The effect of the migration of paraffin wax on the surface free energy of natural rubber (NR) was investigated. The rubber was mixed with the wax and then stored at ambient temperature for up to 168 hrs before its surface free energy was measured using contact angle measurement. Static secondary ion mass spectrometry was also used to provide a chemical fingerprint of the rubber surfaces. The surface free energy decreased as a function of storage time because of the migration of the wax to the rubber surface. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Blooming in rubber may occur when partly soluble compounding ingredient is used at a level in excess of its solubility limit at a given temperature. Blooming is an outcome of a controlled diffusion process [2], while diffusion can be explained as a movement of soluble compounding ingredients driven by a distraction in the equilibrium. Solutions of the compounding ingredient in rubber compound are known to act similarly to solutions of low molecular weight liquids and are characterized by the same laws as for normal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Blooming in rubber may occur when partly soluble compounding ingredient is used at a level in excess of its solubility limit at a given temperature. Blooming is an outcome of a controlled diffusion process [2], while diffusion can be explained as a movement of soluble compounding ingredients driven by a distraction in the equilibrium. Solutions of the compounding ingredient in rubber compound are known to act similarly to solutions of low molecular weight liquids and are characterized by the same laws as for normal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Studies have shown that accelerators, e.g., sulfenamide types, diffuse to the surface because they are partly soluble in most rubbers. 5 This diffusion can be detrimental to rubber properties such as loss of adhesion, 6,7 and also to the durability and performance of rubber in service as well as to health, safety, and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that accelerators, e.g., sulfenamide types, diffuse to the surface because they are partly soluble in most rubbers 3. This diffusion can be detrimental to rubber properties such as loss of adhesion4, 5 and also to health, safety, and the environment.…”
Section: Introductionmentioning
confidence: 99%